Nível de inclusão digital dos alunos do 6º ano das escolas municipais do centro urbano de Assú/RN: necessidades e expectativas - Barbosa, Ana Raquel de Sousa (Universidade Federal Rural do Semi-Árido, 2019)
Nowadays, it is possible to see how much the technologies have advanced and how much they are present in our day to day, either by social or academic, in view of this, this work seeks to investigate the level of digital inclusion of the students of the 6th year of the schools urban schools of the Assu / RN municipal school system, analyze the difficulties presented in relation to the technological infrastructure of the schools used as research field and the obstacles that prevent the use of the technologies by the teachers to later suggest activities that assist in this process. For this work a quantitative research was carried out, where a questionnaire was applied in order to define the level of digital inclusion of the students enrolled in the 6th year of elementary education of the schools of the urban region of the Municipality of Assú / RN. After the questionnaire, analyzes of works with the related theme were performed and then the problems were mapped in order to allow the reader suggestions for solving these problems. As a result of the research, it is possible to understand that the municipal schools of Assú, which have 6th grade elementary school classes, need to invest more in the use of ICTs as tools to aid teaching and learning. Data analysis shows that students and teachers have basic knowledge of computer science, but it is necessary to make better use of this knowledge in the school environment. Finally, we hope that this work can contribute to improving the quality of education through the benefits that technologies offer education, as well as future research in this line of research.
Monografia
Keywords: Inclusão digital; TICs; Escola e ensino; Digital inclusion; TIC; School and teaching; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA